Content Analysis of Social Media on Indonesia Vaccination Covid-19 Policy - Arissy Jorgi Sutan; Zuly Qodir (Universitas Sultan Ageng Tirtayasa, 2021)
The purpose of this study is to determine the types of social media platforms used by proponents and opponents of vaccination. This research employs a qualitative approach, analyzing social media hashtag data with Q-DAS (Qualitative Data Analysis Software) and Nvivo 12Plus. This study finds that: First, social media was used to spread both sides' narratives and content. Second, social media relation tends to be quite strong, but the pro-side is stronger than the contra-side. Third, the narration on both sides uses hashtags and a single word to spread the influence. They were used for vaccination issues on two sides of the issue. This research limitation, like this study concentrating exclusively on social media data, excluded digital data like the phenomenon on social media only. The recommendation for the following research is: Try to understand the social movements opposing or promoting vaccination in Indonesia and compare them to other Asian countries.Keywords: vaccine; policy; social media.